Hadith #2480 - Sahih al-Bukhari - Ady bin Thabit al-Ansari عدي بن ثابت الأنصاري الكوفي (Sahih al-Bukhari)
When I went to Thumama bin `Abdullah, he gave me some perfume and said that Anas would not reject the gifts of perfume. Anas said: The Prophet (ﷺ) used not to reject the gifts of perfume.
Grade: Sahih